Seeking what is right : the Old Testament and the good life - Provan, Iain W. (Iain William), 1957- (Waco : Baylor University Press, 2020)
"A scriptural and historical-theological study of the notion of the flourishing ethical life in Judeo-Christian tradition, with a view toward reading the Old Testament as a guide to the good life"--
Includes bibliographical references and index.
Description based on print version record and CIP data provided by publisher
Keywords: Bible -- Criticism, interpretation, etc; Christian life -- Biblical teaching; Christian life -- History; Conduct of life